Synthesis and biological evaluation of novel N1-phenylsulphonyl indole derivatives as potent and selective 5-HT6R ligands for the treatment of cognitive disorders. (1st November 2016) - Nirogi, Ramakrishna V. S.; Bandyala, Thrinath Reddy; Gangadasari, Pamuletinarasimha Reddy; Khagga, Mukkanti
Abstract: A series of 1-[3-(4-methyl piperazin-1-ylmethyl) phenylsulfonyl]-1 H -indole and 1-[3-(4-ethyl piperazin-1-ylmethyl) phenylsulfonyl]-1 H -indole derivatives were designed and synthesized as 5-HT6 receptor (5-HT6 R) ligands. The lead compound 1-[4-methyl-3-(4-methyl piperazin-1-yl methyl) phenylsulfonyl]-1 H -indole dihydrochloride (6b ), in this series, has shown potent in vitro binding affinity, selectivity, good pharmacokinetics (PK) profile and activity in the animal models of cognition.